OP0089 Combination therapy of selective MMP9 and TNF inhibitors are efficacious in the mouse CIA model of rheumatoid arthritis. (15th June 2017) - Kim, S; Carr, B; Tong, L; Jin, D; Wang, R; Marshall, D; Gossage, D; Smith, V
Abstract : Background: Matrix metalloproteinase-9 (MMP9) is highly expressed by infiltrating inflammatory cells, pannus tissue, and multinucleated cells in the synovium and subchondral bone tissue, including osteoclasts. MMP9 is implicated in rheumatoid arthritis (RA) by its involvement in joint destruction, activation of cytokines and chemokines, and promotion of tissue destruction by degrading the basement membrane of epithelia and vasculature. MMP9 knockout mice are protected from collagen-induced arthritis (CIA) disease progression. A potent, allosteric antibody inhibitor of MMP9 is currently being investigated in clinical trials. The ability of a functional murine analog of this antibody to reduce disease signs and symptoms in established, chronic mouse CIA model both as a single agent and in combination with anti-TNF, was investigated. Objectives: We evaluated the efficacy and safety of selective MMP9 inhibition both alone and in combination with anti-TNF (etanercept), in CIA models of RA. Methods: CIA was induced in male DBA/1J mice (n=15/group) and treatments were administered after disease establishment. Efficacy was assessed via metrics of joint injury including clinical score (erythema/ paw swelling, score 0–4) in addition to histopathological assessment of destructive joint remodeling (soft tissue changes: edema, necrosis, inflammatory cell infiltration, and fibroplasia, sum score 0–16; bone changes: cartilage damage, bone erosion, periosteal bone formation, synovitis, pannus formation, and joint destruction, sum score 0–24). Results: All animals were included in the evaluation. In all endpoints assessed, treatment with each therapeutic agent, on its own or in combination, resulted in improvement with respect to body weight change, clinical score, and histopathological measures. The combination group provided the best overall trend for therapeutic benefit, although statistical significance as compared to each single agent alone was not met in most parameters. Body weight recovery was superior in combination as compared to single agent therapies (52% vs. 12–34%, relative to sham; p<0.05 combination vs. single agents). Clinical score and histopathology measures in soft tissue and bone changes were most improved in the combination therapy group, although it did not achieve statistical significance as compared to each single agent (26% vs. 17–21%; 1.5 vs. 1.5–1.8; and 7 vs. 7–9, respectively). Importantly, combination therapy resulted in a significant number of limbs with zero or mild disease as compared to single agents (no disease sign: 256% vs. 172–223%; mild disease sign: 178% vs. 138–141%). Analysis of complete blood count at the end of study revealed no abnormalities in any treatment group. Conclusions: Selective inhibition of MMP9 was active in reducing disease severity in CIA models of RA. The combination of anti-MMP9 with anti-TNF was well tolerated and increased the number of limbs with no or mild disease compared to anti-TNF alone. Further studies are required to examine combination therapy of selective anti-MMP9 and anti-TNF therapies in a clinical setting. Disclosure of Interest: S. Kim Shareholder of: Gilead sciences, Inc, Employee of: Gilead sciences, Inc, B. Carr Shareholder of: Gilead sciences, Inc, Employee of: Gilead sciences, Inc, L. Tong Shareholder of: Gilead sciences, Inc, Employee of: Gilead sciences, Inc, D. Jin Shareholder of: Gilead sciences, Inc, Employee of: Gilead sciences, Inc, R. Wang Shareholder of: Gilead sciences, Inc, Employee of: Gilead sciences, Inc, D. Marshall Shareholder of: Gilead sciences, Inc, Employee of: Gilead sciences, Inc, D. Gossage Shareholder of: Gilead sciences, Inc, Employee of: Gilead sciences, Inc, V. Smith Shareholder of: Gilead sciences, Inc, Employee of: Gilead sciences, Inc